2015
DOI: 10.1073/pnas.1500396113
|View full text |Cite
|
Sign up to set email alerts
|

CD11b regulates obesity-induced insulin resistance via limiting alternative activation and proliferation of adipose tissue macrophages

Abstract: Obesity-associated inflammation is accompanied by the accumulation of adipose tissue macrophages (ATMs), which is believed to predispose obese individuals to insulin resistance. CD11b (integrin αM) is highly expressed on monocytes and macrophages and is critical for their migration and function. We found here that high-fat diet–induced insulin resistance was significantly reduced in CD11b-deficient mice. Interestingly, the recruitment of monocytes to adipose tissue is impaired when CD11b is deficient, although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 63 publications
3
56
0
1
Order By: Relevance
“…In line with this, mice lacking Col6 show extreme adipocyte hypertrophy without metabolic disease . In line with this, a recent study has shown that deletion of the integrin CD11b inhibits alternative activation and proliferation of adipose tissue macrophages (McGregor et al, 2013;Zheng et al, 2015). Fibrosis is a universal response to inflammation, an attempt of wound healing that occurs in multiple tissues upon chronic inflammation.…”
Section: Extracellular Matrix and Fibrosismentioning
confidence: 84%
“…In line with this, mice lacking Col6 show extreme adipocyte hypertrophy without metabolic disease . In line with this, a recent study has shown that deletion of the integrin CD11b inhibits alternative activation and proliferation of adipose tissue macrophages (McGregor et al, 2013;Zheng et al, 2015). Fibrosis is a universal response to inflammation, an attempt of wound healing that occurs in multiple tissues upon chronic inflammation.…”
Section: Extracellular Matrix and Fibrosismentioning
confidence: 84%
“…In this context, it is of note that in adipose tissue macrophages, the presence of CD11b limits their proliferation and their alternative activation. 56 A further and unexpected surprise was the fact that the erythroid response in Spi-C cell numbers were provided to support this claim). 33 It was argued that heme challenge led to "local differentiation of monocytes into RPMs, thus replenishing the resident population lost by heme toxicity" 4 by adapting a phenotype that is by definition heme-vulnerable?…”
Section: Discussionmentioning
confidence: 98%
“…The majority of macrophages infiltrated in white adipose tissue in obesity co-express CD11b and CD11c [76]. Moreover, CD11b deficient mice are protected from development of HFD-induced insulin resistance through reduction of alterative activation and proliferation of adipose tissue macrophages [77]. CD11c-positive adipose tissue macrophages are identified as markers of insulin resistance in human obesity [78].…”
Section: Ecm Receptors In the Adipose Tissuementioning
confidence: 99%
“…These results suggest that the activation of HA-CD44 pathway regulates macrophage infiltration and inflammation in the adipose tissue of HFD-fed mice. It has been previously shown that the genetic deletion of β2 integrin CD11b protects mice from development of HFD-induced insulin resistance by suppressing the alterative activation and the proliferation of adipose tissue macrophages [77]. …”
Section: Proposed Model For How Ecm-receptor Interaction Is Linkedmentioning
confidence: 99%